An Evaluation of Special Education Teachers’ Professional Formation Programs in Jordan in the Institutions and Centers of Special Education - Al-Khateeb, Akef; Alqadi, Haitham (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed at evaluating the professional formation programs for the teachers of special education during service in the institutions and centers of special education in Jordan. It also aimed at determining the effect of the variables of experience and school type on the degree of obtaining professional formation programs. The study sample consisted of (60) male and female teachers. To achieve the purpose of the study, a tool was designed and consisted of (74) indicators distributed into four major dimensions. The results showed that there was one dimension with a high application degree , which is '' the objectives of the professional training programs'' with a mean of (2.55) whereas there were three main dimensions applied in a medium degree; they are as follows : the dimension of trainers' characteristics , with a mean of (2.23) ; the dimension of programs' content , with a mean of (2.12) ; and the dimension of organizational and administrative aspect , with a mean of (2.00) which ranked finally . The total mean of the tool dimensions was (2.25). The result also showed statistically significant differences at (alpha = 0.05) due to experience in all dimensions and the total degree. However, there were statistically significant differences at (alpha = 0.05) due to institution type.